Aspirin and nonsteroidal anti‐inflammatory drug use and keratinocyte cancers: a large population‐based cohort study of skin cancer in Australia. (1st October 2019) - Pandeya, N.; Olsen, C.M.; Thompson, B.S.; Dusingize, J.C.; Neale, R.E.; Green, A.C.; Whiteman, D.C.; ,
Summary: Background: Nonsteroidal anti‐inflammatory drugs (NSAIDs) have been postulated as chemopreventive agents for basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), but findings from observational studies have been inconsistent, and clinical trial data are scant. Objectives: To examine the association between aspirin and NSAID (nonaspirin) use and the risk of BCC and SCC in a large cohort specifically designed for skin cancer outcomes. Methods: We used data from the QSkin Study, a prospective cohort of 43 764 residents of Queensland, Australia (34 630 were included in this study and 23 581 were used in our primary analyses). We used Cox proportional hazards models to estimate the hazard ratios (HRs) between self‐reported aspirin and NSAID use 1 year prior to study baseline and the first histologically confirmed BCC or SCC for high‐risk (history of skin cancer excisions or more than five actinic lesions treated) and average‐to‐low‐risk participants (no history of skin cancer excision and at most five actinic lesions treated). Results: After a median of 3 years of follow‐up, 3421 participants developed BCC and 1470 SCC (2288 BCC and 932 SCC with complete covariate information). Among the high‐risk group (1826 BCC and 796 SCC), compared with never use, frequent (at least weekly) NSAID use was associated with reduced risk of BCC (HR 0·84, 95% confidence interval 0·71–0.99) but not SCC. Aspirin use was associated with reduced risk of SCC (HR 0·77, 95% confidence interval 0·64–0·93) only among infrequent (less than weekly) users and was not associated with BCC. We observed no association between NSAID or aspirin use and the risk of BCC or SCC among average‐to‐low‐risk participants. Conclusions: While some weakly inverse associations were observed between prior use of aspirin or NSAIDs and skin cancer, the inconsistent patterns of associations do not provide convincing evidence that these medications reduce subsequent skin cancer risk. Further data on doses, duration and long‐term follow‐up may help us to comprehend the cumulative dose effect.